Gasification-based biorefinery integration in the pulp and paper industry: A critical review. (November 2020) - Pio, D.T.; Tarelho, L.A.C.; Pinto, P.C.R.
Abstract: The biorefinery design has attracted interest from the industry and scientific community due to its main role in a future transition to a sustainable bioeconomy. This paper provides a critical review of the integration of biorefinery concepts in the pulp and paper industry, focusing on gasification-based biorefineries, including technological and commercial drivers and barriers, and biorefinery general opportunities and challenges. The pulp and paper industry is commonly recognized as highly suitable to integrate biorefinery concepts. For this purpose, various integrable biorefinery designs composed of distinct conversion processes are proposed in the literature. However, key technologies and biorefinery concepts must firstly be improved and proven at a market level to increase stakeholders confidence. Gasification can be a driving force for this integration and efficient replacement of natural gas by producer gas in burners is the first and most immediate step. Nonetheless, drawbacks associated with the contaminants present in the producer gas (e.g., tars) must be addressed. Research rarely focus on this first step and is more centered on sophisticated gasification applications (e.g., methanol synthesis), without considering associated technological and commercial barriers. Furthermore, supporting policies are generally required to make the integration of biomass gasification technologies in the pulp and paper industry profitable and to avoid the interruption of operation of fully functioning large-scale gasification plants. Highlights: Integration of biorefinery concepts in the pulp and paper industry is reviewed. Gasification-based biorefineries opportunities and drawbacks are discussed. Producer gas has large potential by representing a middle platform compound. Efficient replacement of natural gas by producer gas is a driving force. Government policies and improvement of key technologies are main factors.